Pengaruh Motivasi Intrinsik Dan Ekstrinsik Terhadap Keputusan Berwirausaha Pada Lulusan Perguruan Tinggi Di Kabupaten Tasikmalaya - Winda Yulianti; Ardiansyah; Rina Madyasari; Alfin Nur Arifah (Business, Economics dan Entrepreneurship, 2026)
The high rate of educated unemployment among college graduates is a serious economic challenge, including in Tasikmalaya Regency. Entrepreneurship is a strategic solution to create jobs, but the decision to become an entrepreneur is still a challenge for college graduates in Tasikmalaya Regency. This study uses a causal associative quantitative approach. Sampling was conducted through a non-probability sampling technique with an accidental sampling approach, resulting in 140 college graduate respondents domiciled in Tasikmalaya Regency. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression using IBM SPSS version 25 software. The results of the descriptive analysis showed that intrinsic motivation (3.56) and extrinsic motivation (3.47) were in the high category, while the decision to become an entrepreneur was in the medium category (3.40). Based on the hypothesis test, intrinsic motivation had a positive and significant effect on the decision to become an entrepreneur (thitung = 5.936; Sig = 0.000). Extrinsic motivation also has a positive and significant effect on entrepreneurial decisions (t count = 4.594; Sig = 0.000). Intrinsic motivation was found to have a more dominant influence (B = 0.463) than extrinsic motivation (B = 0.317). Simultaneously, these two variables were able to explain 51.3% of the variation in entrepreneurial decisions (Adjusted R2 = 0.513), while the remainder was influenced by other factors outside the research model.